2014
DOI: 10.3390/e16115919
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Internal Heat Exchanger on Performance of the Transcritical Carbon Dioxide Refrigeration Cycle with an Expander

Abstract: Abstract:The effect of the internal heat exchanger (IHE) on the performance of the transcritical carbon dioxide refrigeration cycle with an expander is analyzed theoretically on the basis of the first and second laws of thermodynamics. The possible parameters affecting system efficiency such as heat rejection pressure, gas cooler outlet temperature, evaporating temperature, expander isentropic efficiency and IHE effectiveness are investigated. It is found that the IHE addition in the carbon dioxide refrigerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…Zhang et al (2014) and J.Shariatzadeh et al (2016) using theoretical approaches based on first and second Law of Thermodynamics evaluated the effect of the IHX in the cycle. They concluded that the IHX increases the specific cooling capacity and the compression work, as well as reduced the optimum working pressure.…”
mentioning
confidence: 99%
“…Zhang et al (2014) and J.Shariatzadeh et al (2016) using theoretical approaches based on first and second Law of Thermodynamics evaluated the effect of the IHX in the cycle. They concluded that the IHX increases the specific cooling capacity and the compression work, as well as reduced the optimum working pressure.…”
mentioning
confidence: 99%
“…However, when the system worked in the expander cycle, use of an IHX reduces the average COP from 2.8 to 2.5 due exergy efficiency loss in the gas cooler, but, in case of the throttling cycle, integration of IHX reduces exergy loss and, as a result, increases the COP from 1.9 to 2.0. Zhang et al [108] carried out a similar study and found that, when IHX is used in an expansion valve cycle, the system performance could increase by 17%. On the contrary, if IHX is used in an ejector cycle, the system performance degrades by 16%.…”
Section: An Auxiliary Component: Internal Heat Exchangermentioning
confidence: 98%
“…Hal ini bertujuan untuk menurunkan temperature masuk ke kompresor. Hal ini terbukti meningkatkan nilai dari COP dari Mesin pendingin sebesar 9.02% dengan jenis Refrigran R410a [5]. Penlitian yang lain juga menunjukkan penggunaan Alat Penukar Kalor Internal pada siklus Pendingin karbon dioksida trankristis dengan expander meningkatkan kapasitas pendingin spesifik dan COP sebesar 17%.…”
Section: Pendahuluanunclassified